Studi Kelimpahan dan Keanekaragaman Tumbuhan Air di Danau Tamblingan, Bali - Ascahya, I Kadek Tobing; Arthana, I Wayan; Wijayanti, Ni Putu Putri (Current Trends in Aquatic Science; Vol 5 No 2 (2022), 2022)
This research aimed to know the diversity abudance and water quality conditions of the life of aquatic plants in Lake Tamblingan. Sampling used methods of observation and purposive sampling. Analysis method used value of diversity indices and abudance. Aquatic plants discovered in Lake Tamblingan were 5 types, divided into 3 types of habitat, namely the type of free floating, floating leaved and emergent. Free float type (free floating) consists of Salvinia molesta, floating-leaved plants (floating leaved) consists of Myriophyllum aquaticum, Nymphoides indica plants sticking out (emergent) consists of Alternanthera philoxeroides, Persicaria decipiens. The highest diversity index value was in stations 3 (far from setlement) of 1,42. The highest abundance value of water plants found in station 2 (close to water recreation site) of 148,20 ind/m² with water plant species of Nymphoid indica. Water quality of DO, pH, Temperature, brightness, depth, nitrate and phosphate showed that the waters of Tamblingan Lake was still on the threshold for the growth of aquatic plants and the diversity was in the medium category.